Geotechnical Properties of Fly Ash Blended Expansive Soil: A Review - Alam, Shamshad; Alselami, Nimer Ali (Civil Engineering Journal, 2024)
Fly ash, an industrial byproduct, is used as both a building material and a soil stabilizer due to its pozzolanic properties. Moreover, it is challenging to extrapolate the results based on an inadequate amount of laboratory data because of the non-homogeneous character of the soil and the diversity in the chemical properties of fly ash. This review article fills in the gaps by providing an overview of the existing data related to the geotechnical characteristics of expansive soil stabilized with fly ash. The chemical composition of fly ash is provided in terms of oxides of various elements to help identify the kinds produced in different nations. Additionally, information about the physical and geotechnical characteristics of fly ash blended expansive soil is provided in order to comprehend the influence of the fly ash's chemical composition and the expansive soil's fines percentage. While the geotechnical property comprises Atterberg's limit, compaction, UCS, shear strength, free swelling index, CBR, and consolidation, the physical property includes specific gravity and durability. Shear modulus, damping ratio, and Poisson's ratio are used to describe the dynamic properties of the modified expansive soil. The published data in this field and the research gap will be identified by the researchers with the aid of this article. Doi: 10.28991/CEJ-SP2024-010-06 Full Text: PDF